1996
DOI: 10.1111/j.1475-6811.1996.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, caregiving, and relationship functioning in couples: Effects of self and partner

Abstract: We examined the links among attachment, caregiving, and relationship functioning in both dating (Study 1) and married couples (Study 2), assessing both partners' perspectives. We found that (1) men and women generally evidenced caregiving characteristics similar to those of their parent% especially their same‐sex parent; (2) individuals who reported giving more care to their partner evidenced less fearful‐avoidant attachment (Studies 1 and 2) and less preoccupation with attachment (Study 2); and (3) individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
119
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 43 publications
14
119
1
5
Order By: Relevance
“…Research findings indicate that secure attachment is positively associated with committed and satisfied relationships, while insecure attachment (a combination of anxious-ambivalent and avoidant attachment patterns) is positively associated with poorer quality relationships (Carnelley, Pietromonaco, & Jaffe, 1996;Collins, 1996;Collins & Read, 1990;Davidovitz et al, 2007;Simpson, 1990). Such research highlights that those with anxious-ambivalent and avoidant attachment patterns experience their relationships differentially, in that adults with avoidant attachment patterns report less commitment and satisfaction than adults with anxious-ambivalent attachment patterns.…”
Section: Theoretical Links Between Attachment Styles Relationship Qumentioning
confidence: 78%
“…Research findings indicate that secure attachment is positively associated with committed and satisfied relationships, while insecure attachment (a combination of anxious-ambivalent and avoidant attachment patterns) is positively associated with poorer quality relationships (Carnelley, Pietromonaco, & Jaffe, 1996;Collins, 1996;Collins & Read, 1990;Davidovitz et al, 2007;Simpson, 1990). Such research highlights that those with anxious-ambivalent and avoidant attachment patterns experience their relationships differentially, in that adults with avoidant attachment patterns report less commitment and satisfaction than adults with anxious-ambivalent attachment patterns.…”
Section: Theoretical Links Between Attachment Styles Relationship Qumentioning
confidence: 78%
“…There was also evidence in Feeney's study that attachment and caregiving have roots in different aspects of childhood experiences with parents. Carnelley, Pietromonaco, and Jaffe (1996), using slightly different measures of caregiving, found that people evidenced caregiving qualities similar to those of their parents, especially their same-sex parent, and that those qualities were associated with current relationship functioning. Camelley et al (1996) concluded that their results "support the idea that attachment and caregiving are central components of romantic love" (p. 257).…”
Section: Integration With Other Behavioral Systemsmentioning
confidence: 99%
“…Fincham et al [69] show, for example, how the level of marital satisfaction crucially controls the kind of attributional bias, which is more benign for the other compared to self in case of a happy relationship, but more negative for the other compared to self in case of a distressful one. On the other hand, the attachment perspective reveals how romantic relationships are directly affected by experiences at pivotal stages of individual developmental histories, as well as by the care-giving style of subjects' same-sex parent [70]. This determines a virtuous vs. vicious circle of affective development moving from security of attachment in early childhood to development of social competence in infancy, to security of relationships in adolescence, and to quality of emotional experiences in early adulthood [71].…”
Section: Attachment Theory: Managing Emotionsmentioning
confidence: 99%